Characteristics of Tonsillopharyngitis Patients at Ibnu Sina Hospital Makassar from January 2023 to May 2024 - Hikma, Nur Suci; Nurmadilla, Nesyana; Pratama, Ahmad Ardhani; Sanna, Andi Tenri; Abidin, Mohammad Reza Zainal (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Upper respiratory tract infections in children often lead to tonsillopharyngitis, which is caused by viruses (such as adenovirus and rhinovirus) or bacteria, especially Group A beta-hemolytic streptococcus (GABHS). Predisposing factors include poor oral hygiene, consumption of certain foods, and inadequate treatment. Objective: To determine the characteristics of age, gender, type of food, clinical manifestations, laboratory results, and management provided to tonsillopharyngitis patients at Ibnu Sina Hospital, Makassar. Results: Of the 86 tonsillopharyngitis patients recorded at Ibnu Sina Hospital, Makassar, between January 2023 and May 2024, the majority of patients were female (60.47%), aged 20-44 years (46.51%). Most patients consumed regular food (74.42%), and the most common clinical symptoms were fever (87.21%), sore throat (75.58%), and hyperemia of the tonsils and pharynx (100%). Laboratory examination showed leukocytosis in 53.49% of patients, and the most common antibiotic treatment was ceftriaxone (55.81%), followed by cefixime (25.58%) Conclusion: The study at Ibnu Sina Hospital, Makassar, concluded that the majority of tonsillopharyngitis patients are female, aged 20-44 years, and consumed regular food. Most patients experienced hyperemia of the tonsils and pharynx, leukocytosis, and were treated empirically with the antibiotic ceftriaxone based on clinical manifestations.